Effect of exercise mode on the blood lactate removal during recovery of high-intensity exercise - Denadai, B. S. [UNESP]; Guglielmo, L. G.A. [UNESP]; Denadai, M. L.D.R. (My University, 2000)
The aim of this study was to determine the effect of exercise mode on the blood lactate removal during recovery of high-intensity exercise. Nine male individuals performed the following tests in order to determine the blood lactate removal: Running - 2×200 m, the subjects ran at their maximum capacity, and rested 2 min between each bout. Swimming - 2×50 m, the subjects swam at their maximum capacity, and rested 2 min between each bout. Each test was realized on different days with three recovery modes: passive (sitting down), swimming, or running. Recovery exercise intensity was corresponding to the aerobic threshold. All recovery activities lasted 30 min. The two forms of active recovery were initiated 2 min after the end of high-intensity exercise and lasted 15 min, and were followed by 13 min of seated rest. After 1,7,12,17, and 30 min of the end of high-intensity exercise, blood samples (25 μl) were collected in order to determine the blood lactate concentration. By linear regression, between the logarithm of lactate concentration and its respective time of recovery, the half-time of blood lactate removal (t1/2) was determined. Time of high-intensity exercise and the lactate concentration obtained in the 1st min of recovery were not different between running and swimming. Passive recovery (PR) following running (R-PR=25.5±4.3 min) showed a t1/2 significantly higher than PR after swimming (S-PR=18.6±4.3 min). The t1/2 of the sequences running-running (R-R=13.0 min), running-swimming (R-S=12.9±3.8 min), swimming-swimming (S-S=13.2±2.8 min), and swimming-running (S-R=8.1±1.3 min) were significantly lower than the t1/2 of the R-PR and S-PR. There was no difference between the t1/2 of the sequences R-R, R-S, and S-S. On the other hand, the sequence S-R showed a t1/2 significantly lower than the sequences S-S and R-R. It was concluded that the two forms of active recovery determine an increase in the blood lactate removal, regardless of the mode of high-intensity exercise performed previously. Active recovery performed by the muscle groups that were not previously fatigued, can improve the blood lactate removal.
Keywords: Blood; Exercise; Lactate; Recovery